Trends in the Development of the Tax System of the Republic of Uzbekistan - Zaripov Khusan Bakhodirovich (Zien Journals, 2022)
This article examines the reforms of the Republic of Uzbekistan in the field of tax policy, changes in the tax system and the views of economists on the tax system of the country. It also analyzes the revenues of the country by type of tax, the revenue of the state budget by type of tax, the indicators of the last three years and the achievements and shortcomings of the tax system. Scientific conclusions and recommendations have been formed in Uzbekistan on the further development of the tax system and, as a result, support for production, improvement of the mechanism of tax incentives
Keywords: tax system; tax policy; taxation; excise tax